ANALISIS FAKTOR KEPUTUSAN PEREMPUAN DI KOTA MALANG UNTUK BEKERJA DI SEKTOR JASA - Zelinka Natalia Angelina; Aminnullah Achmad Muttaqin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The female labor force participation rate has been increasing in recent years, and in the city of Malang, women tend to choose to work in the service sector. This research aims to examine the factors that drive the decision of women in Malang to work in the service sector. The method used is Factor Analysis with the goal of reducing and identifying the main factors or dominant factors that influence the decision of women in Malang to work in the service sector. The research findings indicate two main factors: Family Responsibility and Socio-Economic. Another finding in this study is the tendency of female workers to work in the informal sector, and the growth of the service sector can be seen from the many new professions that have become choices for female workers.